Effects of public trust on behavioural intentions in the pharmaceutical sector: data from six European countries. Issue 6 (3rd June 2021) - Balog-Way, Dominic; Evensen, Darrick; Löfstedt, Ragnar; Bouder, Frederic
Abstract: Few studies have empirically examined the relationship between trust and its consequences in the pharmaceutical context ( e.g. the consequences of trust in medicines advice for patient behaviour). This study empirically examined the European public's perceived trustworthiness of medical, societal, and industry sources of medicines advice, and its consequences for their behavioural intentions including their medicine-taking and information-seeking behaviour. A representative survey ( N = 6, 001) was conducted with adults from six European countries: Great Britain, France, Germany, Denmark, Italy, and Poland. As expected, respondents consistently rated advice from medical sources (GPs, pharmacists, local hospitals, emergency services) as significantly more trustworthy than advice from societal sources (the Internet, friends/relatives, and the mass media) and, especially, industry (pharmaceutical companies and brand specific websites). A structural equation model then revealed strong associations between the public's perceived trustworthiness of these medical, societal, and industry sources and their medicine-taking and information seeking intentions. Important national variations were found including in the public's opinions on when authorities should convey new safety information. Implications for communicating benefit-risk information in a more transparent regulatory environment are discussed, including the importance of maintaining and strengthening trust in medical actors and committing more resources to supporting national risk communication.